“You have to wait for a diagnosis first”: Barriers to preventive mental health support and early interventions for children and young people in Sweden - Karin Törnbom; Dominique Hange; Eva-Lisa Petersson; Irene Svenningsson (PLoS ONE, 2026)
Background Despite increasing attention to youth mental health, children and adolescents in Sweden experience fragmented, inequitable care with regional variation. Delays in diagnosis, limited preventive interventions, and poor inter-sectoral collaboration contribute to significant unmet needs. This study investigates system-level challenges and stakeholder perspectives on opportunities to enhance care pathways. Methods We conducted a qualitative study in the Västra Götaland region, Sweden. Fourteen purposively selected participants – including senior executives, healthcare professionals, and parents took part in semi-structured interviews. We used systematic text condensation, according to Malterud, and the four steps involved in this method for analysing the interviews. Results A central theme across interviews was the requirement for a formal diagnosis before children can access mental health support, particularly in school and primary care settings. Participants described this as a major barrier that delays early intervention and leaves children and young people with complex or atypical presentations without adequate support. Primary care professionals reported increasing mental health caseloads without corresponding increases in staffing or funding, limiting preventive work. Child and adolescent psychiatry (BUP) was described as overwhelmed, with long waiting times and limited continuity of care. A care manager within primary care was proposed as a way to help families navigate fragmented services and improve collaboration, although participants emphasised that such a role would need to be part of broader structural reform. Conclusions Our findings highlight persistent systemic issues in mental health care for children and young people, including inequitable access, insufficient prevention, and fragmented collaboration across sectors. Strengthening primary prevention, reallocating resources to primary and school-based mental health care and implementing well-defined care coordination roles within broader restructuring may improve continuity and equity in service delivery. Comprehensive policy reform is needed to support person-centred, integrated care pathways for children and young people with mental health needs.